Large solitary fibrous tumour of the retroperitoneum: a case report and review of the literature. Issue 4 (November 2013) - Orsaria, M; Marzinotto, S; Mariuzzi, L
Introduction: This report describes an unusual case of a large solitary fibrous tumour (SFT) arising in the retroperitoneum. Case presentation: A 53-year-old woman presented at the Emergency Department with urinary retention and lumbar pain. The urological examination was negative, whereas a presacral retroperitoneal mass was disclosed on ultrasound. The laboratory studies, including tumour markers, were negative. On laparotomy, it was not possible to remove the mass completely due to the difficulty of dissecting it free of the sacrum. Grossly, the fragment had a yellowish-white surface, with areas of necrosis and haemorrhage. On immunohistochemistry, tumour cells were positive for CD34, CD99 and Bcl-2 and negative for CD45, synaptophysin, chromogranin, S100, neuron-specific enolase, CK AE1-AE3, CK7, Wilms' tumour 1, smooth muscle actin, factor VIII, myogenin, epithelial membrane antigen, thyroid transcription factor-1 and CD117, leading to a diagnosis of SFT. Molecular investigation ruled out synovial sarcoma. Conclusion: Although SFT usually has a favourable prognosis, close follow-up is recommended due to the limited information on its long-term behaviour.